2016
DOI: 10.1111/jicd.12219
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet lymphocyte ratio is superior to neutrophil lymphocyte ratio to be used as predictive marker for lymph node metastasis in oral squamous cell carcinoma

Abstract: Preoperative PLR is directly associated with nodal involvement status of OSCC. Preoperative PLR is superior to NLR for predicting LNM in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Preoperative PLR is superior to NLR for predicting lymph node metastases in OSCC. 27 Similar to NLR and PLR, our results also showed that RDW could reflect enhanced inflammation, metastasis, and advanced stage in OSCC patients.…”
Section: Discussionsupporting
confidence: 72%
“…Preoperative PLR is superior to NLR for predicting lymph node metastases in OSCC. 27 Similar to NLR and PLR, our results also showed that RDW could reflect enhanced inflammation, metastasis, and advanced stage in OSCC patients.…”
Section: Discussionsupporting
confidence: 72%
“…All studies were retrospective. Twelve studies were conducted in Asia [11,13,14,16,21–28] and two were performed in Europe [12,15]. The cut-off values for the NLR ranged from 1.77 to 5.…”
Section: Resultsmentioning
confidence: 99%
“…The NLR has been reported to be a significant prognostic marker for a number of malignancies, including colorectal cancer [6], bladder cancer [7], breast cancer [8], ovarian cancer [9], and non-small-cell lung cancer [10]. Recently, many studies have also explored the prognostic and clinical significance of the NLR in oral cancer; however, the results have been inconclusive [11–16]. Therefore, to further verify the prognostic role of the NLR in oral cancer, we conducted a meta-analysis by pooling data from relevant studies.…”
Section: Introductionmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%